2021
DOI: 10.7554/elife.64325
|View full text |Cite
|
Sign up to set email alerts
|

Major genetic discontinuity and novel toxigenic species in Clostridioides difficile taxonomy

Abstract: Clostridioides difficile infection (CDI) remains an urgent global One Health threat. The genetic heterogeneity seen across C. difficile underscores its wide ecological versatility and has driven the significant changes in CDI epidemiology seen in the last 20 years. We analysed an international collection of over 12,000 C. difficile genomes spanning the eight currently defined phylogenetic clades. Through whole-genome average nucleotide identity, and pangenomic and Bayesian analyses, we identified major taxonom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 73 publications
(137 reference statements)
8
84
0
Order By: Relevance
“… C. difficile strains are genetically diverse due to a high rate of genome rearrangement [20, 25] and commonly have variable phenotypes clinically and in culture [26–30]. To determine whether increased tissue oxygenation is a common feature amongst strains during CDI, mice were infected with a C.…”
Section: Resultsmentioning
confidence: 99%
“… C. difficile strains are genetically diverse due to a high rate of genome rearrangement [20, 25] and commonly have variable phenotypes clinically and in culture [26–30]. To determine whether increased tissue oxygenation is a common feature amongst strains during CDI, mice were infected with a C.…”
Section: Resultsmentioning
confidence: 99%
“…The three cryptic clades are extremely divergent (Figs 1 and 2a) and likely represent independent species or subspecies based on the genomic data [14]. Three of the five major clades contain epidemic sequence types (STs); C2 contains ST 1 (corresponding to RT 027), C4 contains ST 37 (RT 017) and C5 contains ST 11 (several RTs, including RT 078) [14]. To date, studies have been conducted on the role of AMR in the emergence and spread of two epidemic STs, 1 and 11 [10, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies using molecular methods indicated a diversity of organisms in the genus Clostridium , and 16S rRNA phylogenetic analysis confirmed that C. difficile had less than 97% similarity with other species from the genus Clostridium . Currently, the genus Clostridioides includes two species, C. difficile and C. mangenotii [ 11 , 48 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%